Cu(OTf)(2) or Et3N-catalyzed three-component condensation of aldehydes, amines and cyanides: a high yielding synthesis of alpha-aminonitriles - Paraskar, Abhimanyu S.; Sudalai, Arumugam (Tetrahedron Letters, 2006)
Copper(II) triflate or Et3N have been found to catalyze, under ambient conditions, the addition of a cyanide anion, such as trimethylsilyl cyanide or acetone cyanohydrin, onto in situ generated imines, furnishing alpha-aminonitriles in excellent yields. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: aldehydes; aminonitriles; multicomponent reactions; organocatalyst; Strecker reaction

Efficient, solvent-free method for the chemoselective synthesis of acylals from aldehydes and their deprotection catalyzed by silica sulfuric acid as a reusable solid acid catalyst - Desai, Uday V.; Thopate, T. S.; Pore, D. M.; Wadgaonkar, P. P. (Catalysis Communications, 2006)
An efficient method has been developed for the chemoselective synthesis of acylals from aldehydes and acetic anhydride in the presence of silica sulfuric acid as a reusable solid acid catalyst under solvent-free conditions. Ketones are found to remain unaffected under the reaction conditions. The deprotection of acylals has also been achieved using SSA in methanol medium. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Acylals; aldehydes; Chemoselective; protection and deprotection silica sulfuric acid

Efficient one-pot synthesis of alpha-amino phosphonates catalyzed by bismuth nitrate pentahydrate - Bhattacharya, Asish K.; Kaur, Tanpreet (Synlett, 2007)
A simple, efficient, and environmentally benign method has been developed for the synthesis of alpha-amino phosphonates through a one-pot reaction of aldehydes with amines and diethyl phosphite in the presence of bismuth nitrate pentahydrate as a catalyst. Some of the major advantages of this protocol are: good yields, the involvement of a less-expensive and non-toxic catalyst, mild and solvent-free reaction conditions and also tolerance towards other functional groups present in the substrates. Eighteen examples are described, highlighting the substrate scope of the reaction.
Keywords: aldehydes; alkyl phosphite; alpha-amino phosphonates; amines; bismuth nitrate pentahydrate; synthetic methods

Organocatalytic activation of TMSCN by basic ammonium salts for efficient cyanation of aldehydes and imines - Raj, I. Victor Paul; Suryavanshi, Gurunath; Sudalai, A. (Tetrahedron Letters, 2007)
Basic ammonium salts act as highly effective catalysts for the cyanosilylation of aldehydes and in Strecker-type aminonitrile synthesis using TMSCN as cyanide source at 25 degrees C under extremely mild conditions, affording very good to excellent yields of silylated cyanohydrins and alpha-aminonitriles. (C) 2007 Published by Elsevier Ltd.
Keywords: aldehydes; aminonitriles; cyanohydrin; cyanosilylation; multicomponent reactions; TMSCN

Amberlite-IR 120 catalyzed three-component synthesis of alpha-amino phosphonates in one-pot - Bhattacharya, Asish K.; Rana, Kalpeshkumar C. (Tetrahedron Letters, 2008)
A simple, efficient, and environmentally benign method for a three-component reaction of an amine, an aldehyde or a ketone, and diethyl phosphite catalyzed by Amberlite-IR 120 resin has been developed to afford alpha-amino phosphonates in high yields and short reaction times under solvent-free reaction conditions. The major advantages of the present method are good yields, inexpensive, ecofriendly and reusable catalyst, mild and solvent-free reaction conditions and tolerance towards various functionalities present in the substrates. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: aldehydes; alkyl phosphite; alpha-amino phosphonates; amines; ion-exchange resin; multi-component reaction

Cu(OTf)(2) catalyzed Biginelli type condensation of aldehydes, beta-keto esters and carbamates: synthesis of 3,4-dihydro[1,3]oxazin-2-ones - Jagdale, Arun R.; Paraskar, Abhimanyu S.; Sudalai, Arumugam (Indian Journal of Chemistry Section B-Organic Chemistry including Medicinal Chemistry, 2008)
Cu(OTf)(2) catalyzes effectively a new multicomponent reaction comprising aldehydes, beta-ketoester and methy carbamate in acetonitrile to afford substituted 3,4-dihydro[1,3]oxazin-2-ones in 60-82% yields. These compounds have been found to show inhibition activity against HL-60 cancer cell.
Keywords: aldehydes; Catalysts; Copper; Multicomponent reaction

Efficient method for the synthesis of acylals from aldehydes under solvent-free conditions catalyzed by antimony trichloride - Bhattacharya, Asish K.; Mujahid, Mohammad; Natu, Arvind A. (Synthetic Communications, 2008)
A mild and efficient method has been developed for the preparation of acylals from aldehydes catalyzed by antimony trichloride under solvent-free conditions in very good to excellent yields. The easy availability, low cost, and ease of handling of the catalyst make this procedure especially attractive for large-scale synthesis.
Keywords: acetic anhydride; Acylals; aldehydes; antimony trichloride; solvent-free conditions

Efficient synthesis of 1,8-dioxo-octahydro-xanthene derivatives promoted by a room temperature ionic liquid at ambient conditions under ultrasound irradiation - Venkatesan, K.; Pujari, Suresh S.; Lahoti, Rajgopal J.; Srinivasan, K. V. (Ultrasonics Sonochemistry, 2008)
The condensation reaction involving an aldehyde and diketone was efficiently promoted by the Ionic liquid, [Hbim]BF(4) (IL) as a reaction medium with methanol as co-solvent at ambient temperature under ultrasonic irradiation to afford the corresponding 1,8-dioxo-octahydroxantliene (xanthene) derivatives in excellent yields. The advantages of this method include among others the use of a recyclable, non-volatile ionic liquid, which promotes this protocol under ambient temperature without the requirement of ally added catalyst. The reaction times and yields are compared with p-TSA catalyzed synthesis of xanthenes under thermal conditions, which is also reported for the first time under our reaction conditions. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: aldehydes; ambient conditions; Bronsted acidity; dimedone; Ionic liquid; Ultrasound; Xanthenes

One-step synthesis of 4-alkyl-3-aryl-2,6-dicyanoanilines and their use in the synthesis of highly functionalized 2,3,5,6,7-and 2,3,4,5,7-substituted indoles - Sawargave, Sangmeshwer P.; Kudale, Ananada S.; Deore, Jaydeep V.; Bhosale, Dattatry S.; Divse, Jaisingh M.; Chavan, Subhash P.; Borate, Hanumant B. (Tetrahedron Letters, 2011)
A three-component, one-step method for the synthesis of 4-alkyl-3-aryl-2,6-dicyanoanilines involving reaction of alkyl aldehyde, malononitrile and aryl aldehyde in presence of morpholine is reported. Highly functionalized 2,3,5,6,7- and 2,3,4,5,7-substituted indoles were prepared from these dicyanoanilines by reaction with ethyl bromoacetate. These substituted dicyanoanilines and indoles have a potential to be converted into various other compounds taking advantage of various functional groups present in these molecules. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: aldehydes; Dicyanoanilines; indoles; Malononitrile

Solvent-free selective oxidation of primary alcohols-to-aldehydes and aldehydes-to-carboxylic acids by molecular oxygen over MgO-supported nano-gold catalyst - Choudhary, Vasant R.; Dumbre, Deepa K. (Catalysis Communications, 2011)
Magnesium oxide supported nano-gold catalyst (prepared by the homogeneous deposition precipitation technique) showed high activity/selectivity and excellent reusability in the oxidation of different primary alcohols and aldehydes to corresponding aldehydes and carboxylic acids, respectively, by molecular oxygen (under atmospheric pressure) in the absence of any solvent. Influence of the catalyst calcination temperature (400-900 degrees C), reaction temperature (50-120 degrees C) and use of different solvents (viz. toluene. p-xylene, DMF or DMSO) on the oxidation reaction has also been studied. (C) 2011 Published by Elsevier B.V.
Keywords: Alcohols; aldehydes; Au/MgO; Molecular oxygen; Solvent-free oxidation

Pd-catalyzed selective hydrosilylation of aryl ketones and aldehydes - Chouthaiwale, Pandurang V.; Rawat, Varun; Sudalai, Arumugam (Tetrahedron Letters, 2012)
Pd salts in combination with triethylsilane as hydride source and DMF as solvent has been found to be excellent catalytic combination that selectively reduces aryl ketones and aldehydes under mild conditions to afford triethylsilyloxy compounds in excellent yields. Product selectivity to the respective benzyl alcohols can however be achieved when the reaction was performed in DMF/H2O (4:1) as solvent system. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: aldehydes; Hydrosilylation; Ketones; Palladium; Triethylsilane

Efficient bakers' yeast-catalyzed multicomponent synthesis of -aminophosphonates in one pot - Bhattacharya, Asish K.; Mujahid, Mohammad (Synthetic Communications, 2013)
Utilizing bakers' yeast (Saccharomyces cerevisiae) as a biocatalyst, synthesis of -aminophosphonates in one pot has been accomplished by the three-component reaction of an aldehyde, an amine, and diethyl phosphite in moderate to good yields under solvent-free reaction conditions. Supplemental materials are available for this article. Go to the publisher's online edition of Synthetic Communications (R) to view the free supplemental file.
Keywords: -aminophosphonates; aldehydes; amines; green chemistry; Saccharomyces cerevisiae; solvent-free conditions

Highly efficient povidone-phosphotungstic acid catalyst for the tandem acetalization of aldehydes to bis- and tris(indolyl)methanes - Kamble, Sumit B.; Swami, Rameshwar K.; Sakate, Sachin S.; Rode, Chandrashekhar V. (ChemPlusChem, 2013)
A novel, nonleachable hybrid of heteropoly acid and polyvinylpyrrolidone (or povidone) catalyzes the acetalization of aldehydes in methanol at room temperature followed by reaction with indole to give bis(indolyl)methanes (BIMs) and tris(indolyl)methanes (TIMs) in quantitative yields (90-97%). The catalyst was shown by pyridine FTIR spectroscopy to possess BrOnsted acidity, and the hybrid formation was confirmed by XRD and (PNMR)-P-31 studies. Friedel-Crafts alkylation of indole as well as the tandem synthesis of BIMs and TIMs were established with several types of carbonyl and indole substrates to give the corresponding products quantitatively. The catalyst was recycled efficiently for three successive runs without losing its original activity.
Keywords: acetals; Acidity; aldehydes; heterogeneous catalysis; heteropoly acids

Croncise organocatalytic route to protected (2S, 4R)-4-hydroxyornithine and(+)-pseudohygroline - Jha, Vishwajeet; Kumar, Pradeep (Synlett, 2014)
A practical, efficient, and organocatalytic approach to the synthesis of (2S,4R)-4-hydroxyornithine and (+)-pseudohygroline is reported using proline-catalyzed sequential alpha-aminoxylation/alpha-amination reaction and Horner-Wadsworth-Emmons olefination reaction of an aldehyde as the key step.
Keywords: aldehydes; Amination; Amino alcohols; cyclization; Enantioselectivity; Wittig reaction

N-Heterocyclic carbene catalyzed oxidative coupling of alkenes/alpha-bromoacetophenones with aldehydes: a facile entry to alpha,beta-epoxy ketones - Reddi, Rambabu N.; Prasad, Pragati K.; Sudalai, Arumugam (Angewandte Chemie-International Edition, 2015)
{A novel, N-heterocyclic carbene (NHC) catalyzed direct oxidative coupling of styrenes with aldehydes has been described for the synthesis of alpha,beta-epoxy ketones in good yields. This unprecedented regioselective oxidative coupling employs NBS/DBU/DMSO (DBU = 1,8-diazabicyclo [5.4. 0] undec-7-ene
Keywords: aldehydes; epoxidation; N-heterocyclic carbenes; Oxidation; synthetic methods

N-heterocyclic-carbene-catalyzed regioselective oxidative ring-opening of epoxides with aromatic aldehydes: a facile entry to alpha-acyloxyketones - Reddi, Rambabu N.; Gontala, Arjun; Prasad, Pragati K.; Sudalai, Arumugam (Asian Journal of Organic Chemistry, 2016)
A high-yielding synthesis of -acyloxyketones using a N-heterocyclic-carbene (NHC)-catalyzed, oxidative ring-opening of epoxides with aromatic aldehydes is described. This regioselective, oxidative process utilizes a N-bromosuccinimide (NBS)/DMSO combination as the oxidant system and Et3N as the base under mild reaction conditions.
Keywords: aldehydes; epoxides; halogen oxidants; N-heterocyclic carbenes; oxygen

Hydroformylation of olefins by metals other than rhodium - Kumar, Rohit; Chikkali, Samir H. (Journal of Organometallic Chemistry, 2022)
Metal catalyzed hydroformylation of alkenes is an atom economic transformation to construct useful aldehydes and is being industrially practiced for decades. The most commonly used metal for this transformation on an industrial scale is rhodium. However, rhodium is rare, costly, and is depleting at a skyrocketing rate. Therefore, finding a suitable alternative to rhodium for metal-catalyzed hydroformylation has been on the radar of many academic and industrial researchers. This review presents the scientific advancements reported in the hydroformylation reaction using metals other than rhodium. An overview of recent progress in palladium, iridium, ruthenium, cobalt, platinum, and iron-catalyzed hydroformylation is presented. Hydroformylation of alkenes and alkynes, using syngas as well as syngas surrogates is examined. The evaluation of the current status of non-rhodium metals in hydroformylation suggests that the field is still in a nascent stage and, except cobalt, no other metal poses a significant challenge to the dominance of rhodium. Deep mechanistic understanding of rate-limiting elementary steps in the non-rhodium metals is largely missing and thus only limited success is reported. Intense research on ligand design, mechanistic understanding, and choice of non-rhodium metal precursors may change this scenario in near future.
Keywords: aldehydes; alkenes; catalysis; Hydroformylation; Non-rhodium metals

Iron-catalyzed magnesium-mediated formal hydroformylation of alkynes and alkenes - Tewari, Tanuja; Kumar, Rohit; Chikkali, Samir H. (ChemCatChem, 2023)
Alkynes and alkenes are routinely converted to corresponding synthetically versatile aldehydes using rhodium-catalyzed hydroformylation. However, rhodium is rare, precious, costly, and depleting at a considerably high rate. Reported here is iron-catalyzed, magnesium-mediated, formal hydroformylation of alkynes and alkenes in the absence of syngas. Readily available FeCl2 in the presence of alkyl magnesium halide, and dimethyl formamide, catalyzes hydroformylation of various alkynes and selectively produces alpha,beta-unsaturated aldehydes in good to excellent conversion. Mechanistic investigations revealed the presence of vinyl magnesium intermediate, the kinetic study disclosed the first-order dependence of the reaction on iron loading, and the control experiment authenticated the iron catalyst's homogeneous nature. The scope of this methodology was amplified, and 20 alkenes were examined. [Fe(acac)(3)] in the presence of ligand, alkyl magnesium halide, and dimethyl formamide catalyzed the hydroformylation of alkenes and displayed good to excellent conversion. An earth-abundant iron catalyst offering a syngas cylinder-free safe alternative to high-pressure hydroformylation has been reported.
Keywords: aldehydes; alkenes; Alkynes; Hydroformylation; iron catalysis